Observation of a large, resonant, cross-Kerr nonlinearity in a cold Rydberg gas - Josiah Sinclair; Daniela Angulo; Noah Lupu-Gladstein; Kent Bonsma-Fisher; Aephraim M. Steinberg (Physical Review Research, 2019)
We report the experimental observation of a cross-Kerr nonlinearity in a free-space medium based on resonantly excited, interacting Rydberg atoms and electromagnetically induced transparency. The nonlinearity is used to implement cross-phase modulation between two optical pulses. The nonlinear phase written onto the probe pulse is measured to be as large as 8 mrad per nanowatt of signal power, corresponding to a χ^{(3)} of 10^{−8}m^{2}/V^{2}. Potential applications range from optical quantum information processing to quantum nondemolition measurement of photon number.